2014
DOI: 10.3109/00207454.2014.896912
|View full text |Cite
|
Sign up to set email alerts
|

White matter involvement beyond the optic nerves in CRION as assessed by diffusion tensor imaging

Abstract: WM appearing normal on brain MRI shows widespread abnormalities in a cohort of CRION patients as assessed by DTI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…However, other white matter areas exhibited changes suggestive of inflammation or demyelination. Therefore, these authors concluded that, in the brains of these patients, a combination of pathological processes seemed to be produced, supporting the hypothesis that CRION is a disorder independent from MS or NMOSD (23).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…However, other white matter areas exhibited changes suggestive of inflammation or demyelination. Therefore, these authors concluded that, in the brains of these patients, a combination of pathological processes seemed to be produced, supporting the hypothesis that CRION is a disorder independent from MS or NMOSD (23).…”
Section: Discussionsupporting
confidence: 55%
“…The only work that studied the impact of CRION on the brain was published by Colpak et al (23), who studied changes in the apparently normal white matter in a group of six CRION patients using DTI. These authors demonstrated widespread effects in the brain that implicated not only the visual tract, as was expected due to the Wallerian degeneration, but also the cerebellum, right superior cerebellar peduncle, body and splenium of the corpus callosum, left thalamus, posterior cingulum, and bilateral posterior bundles of the inferior fronto-occipital tracts, and the inferior longitudinal fasciculi, which exhibited increased fraction of anisotropy (FA) and decreased radial diffusivity (RD).…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been previously shown in the NAWM of patients with chronic recurrent inflammatory optic neuropathy, in T1-hyperintense lesions and normal appearing tissue in patients with MS. The authors attributed these findings to remyelination and glial activation (29,30). Low expanded disability status scale and absence of conversion to MS during the two years of the study may have been partly related to remyelination in the NAWM, occurring as a compensatory mechanism.…”
Section: Discussionmentioning
confidence: 95%
“…The strong response to immuno-suppressive treatment suggests that the etiology of CRION is at least partially immune-mediated. Colpak et al [7] reported that brain white matter (WM) that appeared normal on a brain MRI demonstrated widespread abnormalities in a cohort of CRION patients when assessed via diffusion tensor imaging (DTI). DTI is an advanced MRI technique that allows professionals to evaluate tissue integrity, primarily WM.…”
Section: Discussionmentioning
confidence: 99%
“…DTI is an advanced MRI technique that allows professionals to evaluate tissue integrity, primarily WM. Colpak et al [7] concluded that not only the optic chiasm but also additional WM structures in the brain were affected in patients with CRION. Moreover, their findings may reflect a more complex combination of pathological processes, rather than merely demyelination or axonal degeneration, occurring in the cerebral WM in this particular disease.…”
Section: Discussionmentioning
confidence: 99%